Strategi Efektif untuk Mengatasi Permasalahan Pembelajaran IPS Bagi Guru Sekolah Dasar - Windasari, Rizkika; Lasmawan, I Wayan; Kertih, I Wayan (Jayapangus Press, 2024)
This research aims to identify the problems in Social Studies learning in Elementary Schools and propose effective strategies to address them. This research uses a qualitative descriptive method, with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The research subjects are elementary school social studies teachers with more than 5 years of teaching experience, as well as students in grades 4 to 6. The research results indicate that the main problems in social studies learning include low student interest, lack of use of innovative learning media, and minimal application of active learning methods. Students tend to be passive and do not actively engage in the learning process, while teachers rarely use technology or interactive teaching methods. The proposed strategies to address this issue include the implementation of active learning methods, integration of technology in education, creation of a conducive learning environment, and professional training and development for teachers. With the implementation of these strategies, it is hoped that social studies learning in elementary schools will become more interesting and effective.